Community perceptions of risk factors for interpersonal violence in townships in Cape Town, South Africa: A focus group study - Makanga, Prestige Tatenda; Schuurman, Nadine; Randall, Ellen (Routledge, 2021)
Interpersonal violence is a major contributor to the burden of disease globally, and in South Africa, it is the leading cause of injury. There is an emerging consensus that the development of actionable policy and effective prevention strategies for interpersonal violence requires an understanding of the contextual matters that elevate risk for interpersonal violence. The objective of this study was to explore community perceptions of risks for interpersonal violence in five townships in Cape Town, South Africa, with high rates of violence. Focus group discussions were conducted with community members to identify key factors in that contributed to being either a perpetrator or victim of interpersonal violence. The ecological framework was used to classify the risk factors as occurring at individual, relationship, community or society levels. Some of the risk factors identified included alcohol abuse, poverty, informality of settlements and cultural norms. Differences in how each of these risk factors are expressed and experienced in the five communities are also elucidated. This approach enabled the collection of contextual community-based data that can complement conventional surveillance data in the development of relevant community-level strategies for interpersonal violence prevention.